Forget-me-not / Melati Desa - Desa, Melati (Academy of Language Studies, 2023)
Introduction "Let's go back, I'm tired." said an old fragile lady, who is a mother to my friend during their family outing one fine Sunday evening. At first, her family might have thought she was just exhausted or daydreaming but realization hit them when she started to be aggressive. She has just hit her husband's head ordering him to bring her back home. That was when they realized that something really peculiar must have happened affecting her brain which resulted in such behavior and action. Later, she was unfortunately diagnosed with dementia at just the age of early 60s. Dementia is a syndrome usually of a chronic or progressive nature that leads to deterioration in cognitive functions such as the ability to process thoughts. It affects the memory, thinking, orientation, comprehension, calculation, learning capacity, language and judgment. The impairment in cognitive function is commonly accompanied by changes in mood, emotional control, behavior and motivation. Dementia results from a variety of diseases and injuries which affect the brain, such as Alzheimer's disease or stroke. It brings a big impact and burden on the physical, psychological, social and the economical aspect not only for the patients themselves but also for their caretaker, family and society at large. There is often a lack of awareness and understanding of dementia, resulting in stigmatization and barriers to diagnosis and care. Therefore, in conjunction with the Penang Dementia Awareness Day, the Clinical Research Center of Hospital Seberang Jaya collaborated with the Penang Dementia Association in organizing an event called Forget-Me-Not on 16th October 2022 at the Community Center, Lebuh Acheh.